Nutritional Intervention in Crisis: Formulation of a Ready-to-Eat Rice Meal to Support Disaster Operations in Bulacan - Villanueva, Jacqueline A.; Maroma, Dolly P.; Maroma, Allen N. (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Natural calamities are a major concern in the Philippines, and the province of Bulacan is consistently at the receiving end of these catastrophes, suffering from regular flooding and typhoons that lead to food and nutrition shortages. The goal of this study was to create chicken adobo with rice, a ready-to-eat meal in flexible retort pouches, that guarantees microbiological safety, consumer acceptability, and applicability in disaster relief missions. The product was thermally treated at 240°F (115°C) for 15 minutes at 10 psi, and thereafter, microbiological and sensory evaluations were conducted. Community members, food instructors, and food industry experts comprised the 90 respondents who evaluated product acceptability on a 9-point hedonic scale. The results showed that the RTE rice meal passed the FDA microbiological safety tests, with no trace of Salmonella spp., Listeria monocytogenes, or E. coli. Aerobic Plate Count (APC) and Staphylococcus aureus numbers were below the limit. The sensory evaluation gave the total acceptability score of 7.8 ("like very much"), with excellent ratings for aroma, flavor, and texture. The packaging of flexible retort pouches was found to be the most economical, lightweight, and easy to distribute under disaster conditions. The study concludes that the prepared RTE chicken adobo rice meal is safe, nutritious, and acceptable to the people, thus serving as an effective measure to improve food security and disaster management in Bulacan and other areas affected by disasters.